Ireland’s Haunted Stages - Murphy, Paul (FOCUS: Papers in English Literary and Cultural Studies, 2012)
In this essay I will look at the metaphor of the ghost particularly in relation to the issue of class disparity which has haunted Ireland and its stages for decades and is especially poignant in the current economic situation. Taking my cue from Marvin Carlson’s seminal book The Haunted Stage, I extend his argument that for audiences “ghosting presents the identical thing they have encountered before, although now in a somewhat different context” (7), to the recurrence of class disparity and concomitant social injustice in Ireland as represented in Irish theatre across the twentieth century and on into the contemporary moment. The ghosts that haunt Ireland’s stages re-materialize in the themes, characters and performance accretions of plays in successive decades since 1949. These ghosts are the shades of people whose lives were blighted by injustices perpetrated not by a foreign colonial power, but by domestic class structures that served the interests of a narrow elite at the expense of the broader public.